2023
DOI: 10.1186/s12905-023-02563-1
|View full text |Cite
|
Sign up to set email alerts
|

Roles of increased NUCKS1 expression in endometriosis

Abstract: Background Endometriosis is still a difficult problem for women. The Nuclear Ubiquitous Casein and cyclin-dependent Kinase Substrate 1 (NUCKS1) gene is located on human chromosome 1q32.1. It encodes the NUCKS1 protein, a 27 kDa nuclear DNA binding protein that plays an important role in cell growth and proliferation. NUCKS1 plays an important role in the development of many diseases. However, its role in endometriosis is unclear. Methods Ectopic e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…NUCKS1 exhibits elevated expression levels in ectopic endometrium-like tissues. In vitro studies have revealed that inhibiting NUCKS1 significantly impairs cell proliferation and induces apoptosis in these tissues [71]. Considering the complexity of cyclin B1's role in the proliferation of endometrial cells, it is essential to recognize that increased expression in diseased tissue does not necessarily imply it is the primary factor driving cell proliferation in the specific disease under investigation.…”
Section: Deciphering the Pivotal Role Of Cell Cycle Proteins In Endom...mentioning
confidence: 99%
See 1 more Smart Citation
“…NUCKS1 exhibits elevated expression levels in ectopic endometrium-like tissues. In vitro studies have revealed that inhibiting NUCKS1 significantly impairs cell proliferation and induces apoptosis in these tissues [71]. Considering the complexity of cyclin B1's role in the proliferation of endometrial cells, it is essential to recognize that increased expression in diseased tissue does not necessarily imply it is the primary factor driving cell proliferation in the specific disease under investigation.…”
Section: Deciphering the Pivotal Role Of Cell Cycle Proteins In Endom...mentioning
confidence: 99%
“…The interconnection between NUCKS1, cyclin expression, and the previously discussed relationship highlights its indirect involvement in the regulation of cell cycle processes. This intricate network implicates both cyclins and CDKs in these cellular mechanisms [71].…”
Section: Angiogenesis In the Context Of Cell Cycle Proteins In Endome...mentioning
confidence: 99%